Harapan Baru Atas Pengelolaan Sumber Daya Air terkait Putusan MK Nomor 85/PUU-XI/2013 - Kamala, Izzatin (Jurnal Konstitusi, 2015)
The Decision of Constitutional Court No.85/PUU-XI/2013 (The Decision of CC 2013) has canceled Law No. 7 Year 2004 on Water Resources (Law on WR 2014). The cancellation is a new hope for improving the management of water resources. During the implementation of Law WR 2004, there is mismanagement in the provision of drinking water. This paper has two focus issues, namely: first, how the low responsibility of the state for managing water resources impacts the fulfillment of drinking water for the citizens? Second, how are the improvements of water resources management expected to be realized through the Decision of CC 2013? From the discussion, the author has two conclusions. First, the negligence of the state caused that the role of the state in providing drinking water for the citizens was  lost by the role of private sector. For example, a year before judicial review (2012), the number of consumers of drinking water supplied by the national sector in in the counting unit of household level is only the part of 11.79 percent. The number was lost by the supply of private sector covering 38.85 percent of households nationally. Second, the Decision of CC 2013 brings a new hope. Some basic thought are the improvement of state’s responsibility for managing water resources, termination  on the private’s monopoly and termination on commercialization of water value.